(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The article provides an in-depth analysis of the formation of the system of values within the institution of the family and examines its social and philosophical essence. Values are considered the main spiritual foundation of human life. The study explores the factors influencing their formation within the family, the continuity between generations, social institutions, culture, and trends of modernity. The paper also analyzes how national family traditions are changing in the modern era and how these transformations affect social consciousness and moral standards.